Endast med anden: Att rädda den judiska boken i Europa - Fruitman, Stephen (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1996)
In times of social crisis, like war or economic depression, ethnic groups in the West find themselves compelled to undertake a programme of intensified ethnic invention, in order to justify their continued existence as visible minorities. For the Jewish minority in late-nineteenth and early-twentieth century Europe, the opposing demands made upon it by the twin heritages of the Enlightenment (cultural assimilation into universal ideals) and Romanticism (unique identity as a prerequisite for legitimizing ethnic existence) comprised seemingly unsurmountable contradictions. During the Second World War era, Swedish theologian and cultural critic Marcus Ehrenpreis examined the role of Judaism and Jewish culture in Western tradition. In order to bridge the polarities of universalism and particularism, Ehrenpreis delved back into the Hebrew Bible, paying particular attention to the prophets, and attempted to construct a synthesis of Jewish and European heritages. There he found a tradition pointing the way to negotiating "the good society" in the space between such polarities as individual and society and society and its minorities.